Cardiorespiratory Interactions: Exploring the Impact of Spontaneous and Mechanical Ventilation on Heart Rate Variability - Bubshait, Khlood (Medical Research and Its Applications Vol. 6, 2024)
The purpose of this research method paper is to describe the physiological influence of spontaneous and MV on frequency-based measures of HRV. It has been demonstrated that frequency-based measurements of heart rate variability are a valuable physiological marker that sheds light on how the autonomic nervous system functions in both clinical and research contexts. Because of their physical location within the confined thoracic chamber, the heart and lungs are continuously controlled by the autonomic nervous system during each ventilation cycle. The typical mechanics of the ventilator are altered by mechanical ventilation and its subsequent removal, which results in changes to the intrathoracic pressure, tidal volume, and oxygen supply. A non-invasive method called Heart rate variability (HRV) can be used to evaluate this interaction during ventilation and can be quantified by applying frequency-based measures of the variability between heartbeats. Although HRV is a reliable method to measure the alteration of Autonomic Nervous System (ANS) function and cardiopulmonary interaction, there have been limited reports concerning the changes in the frequency-based measure of HRV during both spontaneous and mechanical ventilation. By understanding the effect of different types of ventilation (spontaneous, MV, weaning process) on the cardiovascular system, the simple determinants of lung-heart interactions will be accurate, provide the most efficient treatment to patients in a critical setting, and consider respiratory support as a confounding variable that might affect the high-frequency measure of HRV in respiratory distress patients with MV, and during the weaning process.